Dynamics of Human Palatal Wound Healing and the Associated Microbiome - Yuan, H.; Chlipala, G.E.; Bangash, H.I.; Meenakshi, R.; Chen, D.; Trivedi, H.M; DiPietro, L.A.; Gajendrareddy, P.; Chen, L. (Journal of dental research, 2025)
Wound healing in the oral mucosa is superior to that in the skin, with faster wound closure accompanied by reduced inflammation, less angiogenesis, and minimal scar formation. A well-characterized oral wound model is critical to investigating the mechanisms of oral wound closure and the efficacy of various clinical interventions. Currently, there are a few human oral wound models, although none of them are well characterized. In the present study, we describe and characterize a human hard palate wound healing model. A 3.5-mm circular and two 1 × 5-mm rectangular full-thickness wounds were made in the first and second molar region, 5 mm from the gingival margin, on the hard palate of human subjects. The circular wound was used to monitor wound closure and collect swabs for a microbiome analysis via 16s rRNA sequencing. The rectangular wounds were biopsied and the tissue was used to evaluate the gene expression of wound healing-related mediators by real-time polymerase chain reaction. Saliva was also collected to examine the protein levels of similar molecules by enzyme-linked immunosorbent assays. Circular wounds were nearly closed on day 7 after wounding. Significant changes in the gene expression of inflammatory cytokines, growth factors, antimicrobial peptides, and extracellular matrix-related molecules were identified in day 1 and day 3 wound tissue and compared with unwounded tissue on day 0. Changes in the protein levels of various mediators were limited in the saliva. In addition, alpha diversity, beta diversity, and differential microbiome analysis demonstrated significant changes in bacterial colonization of the wound surface over time compared with unwounded mucosa. In summary, we comprehensively characterize a human hard palate wound-healing model that details the dynamic changes of wound closure, levels of wound healing-related mediators in the wound and saliva, and the oral wound microbiome.